“We Are More than Our Parents’ Mental Illness”: Narratives from Adult Children - Pamela M. Patrick (International Journal of Environmental Research and Public Health, 2019)
Although research on children of parents with mental illness is growing, few researchers have examined the long-term impact of parental mental illness on adult children. This study explored the potential impact growing up with a parent with a mental illness on the parenting role assumed by adult children. The qualitative study included ten participants, who were individually interviewed using a semi-structured interview schedule. Interpretative phenomenological analysis (IPA) along with member checks were utilised to derive themes from participants’ narratives. Three main themes were identified, including: ‘this is me’, ‘a whole new world’, and ‘because of you’. ‘This is me’ consisted of narratives highlighting how adult children intentionally went about parenting in ways different from their parents, and ‘a whole new world’ captured the salient identity that parenthood served for adult children. The third theme, ‘because of you’ highlighted the challenges adult children faced in their parenting roles as a result of their childhood experience living with a parent with mental illness. Participants highlighted the main challenges to be an absence of a reference point and lack of informal social supports. Recommendations for mental health practitioners and future research are presented in order to develop better ways to support adult children and their families.